Coastal conservation - Maslo, Brooke, 1979-; Lockwood, Julie L. (Cambridge : Cambridge University Press, 2014)
Coastal ecosystems are centres of high biological productivity, but their conservation is often threatened by numerous and complex environmental factors. Citing examples from the major littoral habitats worldwide, such as sandy beaches, salt marshes and mangrove swamps, this text characterises the biodiversity of coastline environments and highlights important aspects of their maintenance and preservation, aided by the analysis of key representative species. Leaders in the field provide reviews of the foremost threats to coastal networks, including the effects of climate change, invasive species and major pollution incidents such as oil spills. Further discussion underscores the intricacies of measuring and managing coastline species in the field, taking into account the difficulties in quantifying biodiversity loss due to indirect cascading effects and trophic skew. Synthesising the current state of species richness with present and projected environmental pressures, the book ultimately establishes a research agenda for implementing and improving conservation practices moving forward.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Coastal ecology; Coastal ecosystem health; Shore protection